Pengaruh Model Pembelajaran Talking Stick Berbantu Media Question Box Terhadap Belajar IPA - Dewi Pradina, Nofita; Japar, Muhammad; ukmarani, Dhuta S (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the effect of the Talking Stick model assisted by the Question Box media on the science learning outcomes for fourth grade students at Mojotengah Village, Kedu District, Temnggung Regency. This research is a type of Pre- Experimental Design research, with the One Group Pretest-Posttest Design model. Samples had taken as many as 20 students used as an experimental class. The sampling technique used saturated sampling. Data collection used the test method. This test is used to test the extent to which students experience changes in science learning outcomes before and after being treated. The analysis used in this study is the Wilcoxon Signed Rank Test with SPSS version 16.0. The results showed the Talking Stick model assisted by the Question Box media on the science learning outcomes. Evidence of an increase in students science learning outcomes is a significant difference between the pretest score and the posttest score, the average pretest score 0f 62.45 while the posttest score is 80.3. This is supported by the existence of a hypothesis test conducted with the Wilcoxon Signed Rank Test, the Z obtained score -3.729. with Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). based on the results of the analysis and discussion there was an increase of 17.85 from the average results of the preest and posttest. The results of this research can be concluded that the use of Talking Stick model assisted by the Question Box media has a significant effect on the science learning outcomeson the theory style and motion